2019
DOI: 10.1158/1078-0432.ccr-18-1763
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy Targeting HPV16/18 Generates Potent Immune Responses in HPV-Associated Head and Neck Cancer

Abstract: Purpose: Clinical responses with programmed death (PD-1) receptor directed antibodies occur in about 20% of patients with advanced head and neck squamous cell cancer (HNSCCa). Viral neoantigens, such as the E6/E7 proteins of HPV16/18 are attractive targets for therapeutic immunization, and offer an immune activation strategy that may be complementary to PD-1 inhibition. Experimental Design: We report Phase Ib/II safety, tolerability and immunogenicity results of immunotherapy with MEDI0457 (DNA immunotherapy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 45 publications
2
106
0
Order By: Relevance
“…In the clinic McNeel et al reported that combination anti-PD-1 immunotherapy with a T-cell stimulating DNA vaccine was well-tolerated and promoted antitumor responses [25]. A more recent study by Agarwall et al tested the adaptive EP delivery of a synHPV vaccine for treatment of HPV positive head and neck cancers [26]. This phase Ib/II safety, tolerability, and immunogenicity study reported results of immunotherapy with MEDI0457 (DNA immunotherapy targeting HPV16/18 E6/E7 co-delivered with plasmid IL12) delivered by adaptive CELLECTRA-EP.…”
Section: Immunotherapy For Viral Diseasesmentioning
confidence: 99%
“…In the clinic McNeel et al reported that combination anti-PD-1 immunotherapy with a T-cell stimulating DNA vaccine was well-tolerated and promoted antitumor responses [25]. A more recent study by Agarwall et al tested the adaptive EP delivery of a synHPV vaccine for treatment of HPV positive head and neck cancers [26]. This phase Ib/II safety, tolerability, and immunogenicity study reported results of immunotherapy with MEDI0457 (DNA immunotherapy targeting HPV16/18 E6/E7 co-delivered with plasmid IL12) delivered by adaptive CELLECTRA-EP.…”
Section: Immunotherapy For Viral Diseasesmentioning
confidence: 99%
“…The most common AE was grade I/II injection site pain. No grade III/IV AEs were reported . Finally, in a current phase Ib/II study, the combination of durvalumab and MEDI0457 is being evaluated as second‐line treatment in HPV‐16‐ or HPV‐18‐associated R/M HNSCC.…”
Section: Small Moleculesmentioning
confidence: 99%
“…No grade III/IV AEs were reported. 61 Finally, in a current phase Ib/II study, the combination of durvalumab and MEDI0457 is being evaluated as second-line treatment in HPV-16-or HPV-18-associated R/M HNSCC. Safety, efficacy, and immunogenicity will be evaluated.…”
Section: Medi0457mentioning
confidence: 99%
“…HPV E6 and E7 oncoproteins represent ideal targets for this type of therapeutic intervention because of their constitutive expression in HPV associated tumors and their crucial role in the induction and maintenance of HPV associated diseases [11]. To that end, our previous clinical studies of HPV-specific immunotherapy engendering T cell responses have shown to translate in clinical benefit for woman exhibiting advanced dysplastic cervical lesions as well as patients with HPV associated squamous cell carcinoma of the head and neck [11,12].…”
Section: Introductionmentioning
confidence: 99%